SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL STUDIES ON IRON (II) COMPLEX OF SCHIFF BASE DERIVED FROM ORTHOPHENYLENEDIAMMINE AND 2-NITROBENZALDEHYDE - Muhammad, Sani; Bashir , A.; Saeed, A. (FUDMA JOURNAL OF SCIENCES, 2024)
The synthesis and characterization of Schiff base derived from Orthophenylenediammine and 2-Nitrobenzaldehyde and its Iron (II) complex were undertaken. It was prepared by the condensation reaction of Orthophenylenediammine and 2-Nitrobenzaldehyde. Its Iron (II) metal complex was synthesized by coupling Iron (II) chloride with the formed ligand. These ligands and their complexes were characterized on the basis of their melting point and Decomposition temperature of the Schiff base and metal(II) complexes respectively, infrared spectral analysis, Solubility test, conductivity Test and magnetic susceptibility measurement. The ligand was found to be yellow in colour with a percentage yield of 50% and melting point of 265ºC, The Iron (II) complex was found to be Redish brown in colour with 55% percentage yield and 300ºC decomposition temperature, The ligand and the Iron (II) complex were found to be insoluble in water, n-hexane and Acetone and slightly soluble in methanol and ethanol and completely soluble in Dimethyl sulphoxide, The Iron (II) complex was found to be paramagnetic in nature, A band at 1525cm-1 of the ligand showed that the Aldehyde coordinated with the primary amine.
Keywords: Ligand; Complexes; Orthophenylenediammine; 2-Nitrobenzaldehyde